Developing English Speaking Materials for Tenth Grade Students of Conversation Program at Madrasah Aliyah (MA) Ali Maksum - Kurniasih, Ayu; Lisan, Khusnul Harsul (JETLEE: Journal of English Language Teaching, Linguistics, and Literature, 2023)
The purpose of this study is to develop English learning materials for MA Ali Maksum's Conversational Program. Because the presence of English materials in speaking classes is critical, material development may aid students in learning. Materials that help students improve their skills and motivate them are those that are personalised to the student's situation and background. This research and development (R&D) study employs the ADDIE instructional design model. This research consists of needs analysis, syllabus design, English speaking material development, product validation, product testing, and final product. Interviewees include experienced English teachers, an expert in English materials design, and 10th grade students from MA Ali Maksum's Conversation Program. Student questionnaires, student and teacher interview guides, and validation sheets for expert judgment are among the data collection tools used. The data obtained were analyzed quantitatively and qualitatively. The result showed that the average interval for the English module was 2.26 x 3.24, and material expert validation ranged from 2.80 to 3.40, classifying this module as good and valid with several revisions. Therefore, this English module can be used to motivate students while also assisting them in learning English in a speaking or conversation context.